Redox-mediated 3D graphene based nanoscoop design for ultracapacitor applications - Rani, Pallavi; Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (New Journal of Chemistry, 2017)
Contemporary energy storage devices significantly rely on the rational design of micro and nanostructural features of electrode materials for efficient ion transport. A judicious concept of utilizing the extended charge mobility on the third dimension along with an active redox couple to significantly maximize the capacitance has been demonstrated via (a) the fabrication of a 3D network from 2D graphene and (b) the introduction of an active redox species. Compared with traditional graphene systems, an unprecedented 8-fold gain of capacitance that was sustained with minimal loss even beyond 5000 cycles is achieved and is reported for the first time. This was due to the complementary advantage of both the electric double layer capacitance of the 3D graphene electrode and the redoxmediated pseudocapacitance of K3Fe(CN)(6) in alkaline electrolytes. Colloidal polystyrene spheres with a tunable size range were used as sacrificial templates for generating the 3D network. This design outperforms others, is an excellent candidate as an ultracapacitor and is envisaged to lead to new opportunities in several electrochemical applications.